In vitro growth inhibition, molecular mechanisms of cell cycle arrest, and apoptosis in prostate cancer cells by SRJ23 - Wong, Hui Chyn (2013)
SRJ23 (3, 19-(3-chloro-4-fluorobenzylidene andrographolide), a new semisynthetic derivative of andrographolide (AGP) was shown to exhibit selective anticancer activity against the hormone-independent prostate cancer cell lines (PC-3 and DU-145) in the USA National Cancer Institute (NCI) in vitro anticancer screen. Hence, in this study SRJ23 was investigated further for its mechanisms of cell cycle arrest and apoptosis. The microculture tetrazolium (MTT) assay was utilized in assessing the in vitro growth inhibition and cytotoxicity of SRJ23 and its parent compound, AGP against three human prostate cancer cell lines (PC-3, DU-145 and LNCaP). Subsequently, flow cytometry was used to analyse the cell cycle distribution of treated cells. Fluorescence microscopy was performed to determine the morphological cell death. DNA fragmentation and annexin V-FITC/PI flow cytometry analyses were carried out to confirm apoptosis induced by SRJ23. Quantitation of cell cycle and apoptotic regulatory proteins were determined by western blot analysis. SRJ23 was found to be more potent than AGP in exerting growth inhibition and cytotoxicity. The activity of the compound was selective towards PC-3 cells and induced G2/M arrest which led to predominantly apoptotic mode of cell death. The internucleosomal DNA fragmentation induced by SRJ23 was inhibited in the presence of caspase 8 inhibitor (Z-IETD-FMK). To induce G2/M cell cycle arrest, the compound downregulated CDK1 without affecting the levels of CDK4 and cyclin D1. Interestingly, the compound induced G1 cell cycle arrest in LNCaP and DU-145 cell lines, which attributed to increase expression of p21 and downregulation of CDK4 and cyclin D1 but without affecting the levels of CDK1. Additionally, SRJ23-treated LNCaP cells showed increased levels of wild-type p53. However, the compound did not affect mutant p53 level in DU-145 cells. AGP also induced G1 arrest in both the cell lines via increased the expressions of p21 and downregulated CDK4 but without affecting the levels of CDK1 and cyclin D1. However, unlike SRJ23, it did not affect the wild-type p53 protein in LNCaP cells. The induction of apoptosis by SRJ23 is associated with increased caspase 8 expression and activation. This thought to have induced cleavage of Bid into tBid. Additionally, expression and activation of executioner caspase 9 and pro-apoptotic Bax proteins, with a concomitant down-regulation of the anti-apoptotic Bcl-2 protein level were noted in all the three prostate cancer cell lines. AGP produced similar effects except it failed to affect Bcl-2 protein level in all three prostate cancer cell lines. Therefore, based on these findings, SRJ23 is proven to be more potent than AGP in inducing growth inhibition, cell cycle and apoptosis. The molecular events related to these effects have been established and undoubtedly points to the fact that some of pathways involved in SRJ23‟s anticancer effect differ compared with AGP. As such the former is being considered a lead compound in the discovery of clinical anti-prostate cancer agents.